Chicken histone H5 mRNA: the polyadenylated RNA lacks the conserved histone 3' terminator sequence. - Krieg, P A (1982)
Using 3 overlapping cDNA clones we have determined the nucleotide sequence of chicken histone H5 mRNA. The mRNA does not contain the 23 base conserved sequence element that is present at the 3' end of cell-cycle regulated histone mRNAs. Although the RNA is polyadenylated it lacks the 3' AAUAAA sequence.